Wissenschaft des Judentums beyond tradition: Jewish scholarship on the sacred texts of Judaism, Christianity, and Islam - Salzer, Dorothea M.; Gafni, Chanan; Harif, Hanan (De Gruyter, 2019)
The scholarly study of the texts traditionally regarded as sacred in Judaism, Christianity, and Islam has been an important aspect of Wissenschaft des Judentums and was often conceptualized as part of Jewish theology. Featuring studies on Isaak Markus Jost's Jewish children's Bible, Samson Raphael Hirsch's complex position on the question whether or not the Hebrew Bible is to be understood within the context of the Ancient Orient, Isaac Mayer Wise's "The Origin of Christianity," Ignaz Goldziher's Scholarship on the Qur'an, modern translators of the Qur'an into Hebrew, and the German translation of the Talmud, the volume attempts to shed light on some aspects of this phenomenon, which as a whole seems to have received few scholarly attention, and to contextualize it within the contemporary intellectual currents.